TIPOLOGI DAN MOTIVASI MASYARAKAT PEMELIHARA NURI TALAUD SEBAGAI BURUNG DILINDUNGI DI PULAU KARAKELANG - Diah Irawati Dwi Arini; Isdomo Yuliantoro (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2016)
Nuri talaud is a member of  parrot and status listed as rare, endangered, endemic and protected bird species. Interesting feather color, sound and scarcity are the main attraction making nuri talaud as a pet. The aim of  this study was to determine the typology and motivation of  Karakelang community towards ownership nuri talaud and to observe people's knowledge on conservation of  the species. The research was conducted in the Bantane, Bengel and North Beo Villages. Retrieval of  data was held in November-December 2014 with a survey method by including interviews and observation. Data were analyzed by using Chi Square test (χ2) and descriptive qualitative method. The results showed that, firstly, 92.6% were in the age 15-59 years, 77.7% respondents were graduated form elementary and junior high school, 63.0% of  them are farmers, 74.1% were dominated by male, 81.5% were local people of  Karakelang Island and 70.3% lived in rural areas. Secondly, rural communities were generally keep nuri talaud with an economic motivation for trading , whereas urban communities maintain it for hobbyst as pets. Thirdly, status of  nuri talaud as endangered birds were generally known by the communities, however illegal trade of  this species was still continue due to lack  of  enforcement.